2013
DOI: 10.1080/17445647.2013.799050
|View full text |Cite
|
Sign up to set email alerts
|

Morphotectonic map of the Aventino-Lower Sangro valley (Abruzzo, Italy), scale 1:50,000

Abstract: This work presents the Morphotectonic map of the Aventino-Lower Sangro valley, located in the southern Abruzzi area, and extending from the Apennines chain to the eastern piedmont, from the Maiella Mountain to the Adriatic coast. It is the result of an extensive drainage basin scale geomorphological analysis carried out in the Abruzzi area and incorporates four main sections: orography and hydrography (upper right on the map); morphotectonic section (centre and left on the map); quaternary fluvial deposits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
(40 reference statements)
1
38
0
Order By: Relevance
“…The Adriatic Piedmont landscape (D'Alessandro et al 2003(D'Alessandro et al , 2008Paron 2004;Della Seta et al 2008;Buccolini et al 2010;Miccadei et al 2012cMiccadei et al , 2013; for surrounding areas see also Coltorti et al 1991Coltorti et al , 1996Giannandrea et al 2014 started to develop more recently, during the emersion phase that occurred in the late Early Pleistocene (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Adriatic Piedmont landscape (D'Alessandro et al 2003(D'Alessandro et al , 2008Paron 2004;Della Seta et al 2008;Buccolini et al 2010;Miccadei et al 2012cMiccadei et al , 2013; for surrounding areas see also Coltorti et al 1991Coltorti et al , 1996Giannandrea et al 2014 started to develop more recently, during the emersion phase that occurred in the late Early Pleistocene (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Early Pleistocene, it has been located in its present position near the outer and more superficial thrusts. In this area, geomorphological studies and mapping (D'Alessandro et al 2008;Della Seta et al 2008;Miccadei et al 2012cMiccadei et al , 2013 have shown the development of intense selective erosion processes induced by the regional uplift and controlled by the passive role of morphostructures and lithology in terms of hardness, fracturing and erodibility. These processes resulted in the formation of major thrust ridges (Gran Sasso, eastern Morrone) and exhumed anticlinal ridges (Maiella) along the chain front.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field survey (scale 1:10,000) was carried out in the years 2013-2016, investigating bedrock, Quaternary continental (post-orogenic) deposits, and the main morphotectonic elements (Centamore et al, 1996;Chelli, Segadelli, Vescovi, & Tellini, 2015;Ciccacci, Fredi, Lupia Palmieri, & Salvini, 1986;Griffiths, Smith, & Paron, 2011;Miccadei et al, 2013;Panizza & Castaldini, 1987;Picotti, Ponza, & Pazzaglia, 2009). Morphotectonic elements were classified according to their location in the landscape (ridges, slopes, valleys, hydrography forms, and fluvial terraces) and morphogenetics.…”
Section: Methodsmentioning
confidence: 99%
“…As part of an extensive geomorphological analysis in the central-eastern Apennines (Miccadei, OrrĂą, Piacentini, Mascioli, & Puliga, 2012b;Miccadei, Piacentini, Dal Pozzo, La Corte, & Sciarra, 2013;Miccadei, Piacentini, Gerbasi, & Daverio, 2012a;Piacentini, Sciarra, Miccadei, & Urbano, 2015;Piacentini, Urbano, Sciarra, Schipani, & Miccadei, 2016;Santo et al, 2014;Sciarra, Coco, & Urbano, 2016), this map provides a basis for the study of morphotectonic features at basin-scale and the reconstruction of paleo-landscapes with special regard to drainage network evolution.…”
Section: Introductionmentioning
confidence: 99%